1983
DOI: 10.1136/bmj.287.6386.167
|View full text |Cite
|
Sign up to set email alerts
|

Improved tumour localisation using indium-111 labelled antibodies.

Abstract: Immunoglobulin G (IgG) antibodies to carcinoembryonic antigen (CEA) were labelled with radioactive indium

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1983
1983
1991
1991

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…The amount accumulated, however, is so low that detectable contrast from normal tissues cannot be reliably achieved by external scanning. Attempts to increase the tumour to normal tissue contrast have evaluated different isotopes (Fairweather et al, 1983b;Rainsbury, 1984) and different methods of scanning such as emission tomography (Berche et al, 1982). These techniques, however, are methods of improving the sensitivity of the detection of the very small amounts of labelled antibody accumulated by tumours.…”
Section: Discussionmentioning
confidence: 99%
“…The amount accumulated, however, is so low that detectable contrast from normal tissues cannot be reliably achieved by external scanning. Attempts to increase the tumour to normal tissue contrast have evaluated different isotopes (Fairweather et al, 1983b;Rainsbury, 1984) and different methods of scanning such as emission tomography (Berche et al, 1982). These techniques, however, are methods of improving the sensitivity of the detection of the very small amounts of labelled antibody accumulated by tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Indium 111 meets these requirements, and tumor uptake of antibodies labelled with it is generally higher than with iodine-labelled antibodies (Fairweather et al 1983). The prototype of a hand-held gamma probe has been developed for use with 11 aIn, and the efficiency of this detection method was evaluated in ten patients operated on for colorectal carcinoma.…”
Section: Introductionmentioning
confidence: 96%
“…Several papers have revealed the advantages of using In-111 instead of 1-131 labeled MoAb for radioimmunolocalization studies [39,40]. Generally, In-111 label offers greater tumor-to-blood ratios at a faster rate, higher level and longer retention time of radioactivity in the tumor, hence clearer radio-scintigrams of the tumor are obtained than with 1-131 [41,42].…”
Section: Selection Of Radionuclides 1 Radionuclides Of Halogens Omentioning
confidence: 99%
“…The relatively rapid excretion of iodine from labeled antibodies has been cited as evidence for systemic deiodination of antibodies [199,220]. A second and more likely explanation is that both labels catabolized equally rapidly at the tumor site [221,222], but while liberated radioiodine is removed and excreted, In-111 is retained in the tumor [39,199,223]. Khaw et al [224] reported that In-111 to 1-131 ratio of an In-111 and 1-131 dual-labeled MoAb in blood kept at unity, but increased gradually in the tumor.…”
Section: Comparison Of Biodistribution Of In-1 11 and Radioiodine Labmentioning
confidence: 99%